Epidemiological profile of young people with mental and behavioral disorders in the state of Piauí, Brazil (Research, Society and Development, 2023)
The relevance of mental health in childhood and adolescence has become more focused in recent years. Therefore, it aimed to analyze the epidemiological profile of psychological disorders in children and adolescents from 2018 to 2022, in the state of Piauí. This is a descriptive and exploratory study, carried out in the SUS Hospital Information System (SIH/SUS). A total of 832.899,71 cases of psychiatric and behavioral disorders were evaluated in children and adolescents aged 1 to 19 years, reported in Piauí, with an annual average of 166.579,94 cases. More frequently in males (81.3%), aged 15 to 19 years (89.8%), and mixed race (86.6%). Overall, 30.8% were cases of disorders due to the use of other psychoactive substances, and among females, mood disorders were more frequent (35.8%). It is believed that identifying the prevalence of these disorders in this group can significantly help in the implementation of early and appropriate treatment, improving the prognosis for adult life.